Dysregulation of metabolic enzymes in tumor and stromal cells: Role in oncogenesis and therapeutic opportunities. (31st March 2020) - Khan, Mohammad Aslam; Zubair, Haseeb; Anand, Shashi; Srivastava, Sanjeev Kumar; Singh, Seema; Singh, Ajay Pratap
Abstract: Altered cellular metabolism is a hallmark of cancer. Metabolic rewiring in cancer cells occurs due to the activation of oncogenes, inactivation of tumor suppressor genes, and/or other adaptive changes in cell signaling pathways. Furthermore, altered metabolism is also reported in tumor-corrupted stromal cells as a result of their interaction with cancer cells or due to their adaptation in the dynamic tumor microenvironment. Metabolic alterations are associated with dysregulation of metabolic enzymes and tumor-stromal metabolic crosstalk is vital for the progressive malignant journey of the tumor cells. Therefore, several therapies targeting metabolic enzymes have been evaluated and/or are being investigated in preclinical and clinical studies. In this review, we discuss some important metabolic enzymes that are altered in tumor and/or stromal cells, and focus on their role in supporting tumor growth. Moreover, we also discuss studies carried out in various cancers to target these metabolic abnormalities for therapeutic exploitation. Highlights: Cancer cells make adaptive changes in their cellular metabolism to maintain proliferative state and survival. Transformed cellular metabolism is associated with dysregulation of metabolic enzymes. Metabolic rewiring in stromal cells is also observed likely facilitated through tumor-derived factors. Altered release of metabolic derivatives by the tumor and stromal cells further alters the tumor microenvironment. Tumor-stromal metabolic crosstalk is vital for tumor growth providing opportunities for therapeutic exploitation.